Optimal performance of microgrid in the presence of demand response exchange: A stochastic multi-objective model. (March 2019) - Khalili, Tohid; Nojavan, Sayyad; Zare, Kazem
Abstract: This paper investigates optimal scheduling of the microgrids, including renewable energy sources and conventional generators. Due to the stochastic nature of the wind speed and the sun irradiation, generated power of the wind turbines and photovoltaic are highly uncertain and in the proposed model the uncertainty of the load, price, and renewable energy sources generation are considered by utilizing the normal distribution function. Incentive-based demand response program is implemented in the operating process. The optimal economic status is achieved by maximizing the microgrid's demand response program profit and minimizing the generators cost, and the trading cost. This multi-objective model is solved by the weighted sum technique in order to produce the optimal Pareto solutions and the trade-off solution is selected by applying the fuzzy satisfying method. It is performed on two different microgrids and sensitivity analysis is executed. Results demonstrate that demand response program reduces unused energy in both scenarios.